The Role of Science Teachers’ Awareness in their Classroom Practice of Formative Assessment - Kaya, Gökhan; Atasoy, Volkan; Candan-Helvacı, Sevcan; Pektaş, Murat (Turkish Education Association, 2020)
The aim of this study is to determine the awareness of science teachers of formative assessment and to examine how formative assessment awareness is reflected in teachers’ classroom practices. For this purpose, the exploratory mixed method was used in the study. For the first part of the study, the quantitative dimension was composed of 33 teachers, and the second part of the qualitative aspect consisted of 4 science teachers. As a data collection tool, a formative evaluation interview form consisting of 7 open-ended questions developed by the researchers and in-class observation form focusing on teachers' practices were used. The data obtained were analyzed by content analysis, and themes and codes were created. For the analysis of this data collection tool, a theme-code list was formed based on the data obtained in the research. As a result of the analyses, the teachers were divided into three levels: naive, eclectic and conscious. The majority of teachers who participated in the study were at the eclectic level. Teachers at this level have fundamental knowledge about the importance and use of formative assessment; however, it was found that these teachers do not adequately reflect the formative assessment in their practice. It was also observed that there was a parallel between teachers' awareness of formative assessment and their classroom practices. Considering the results obtained in this study, it is concluded that increasing the teachers’ awareness regarding formative assessment can directly affect the shaping of their classroom practices.
Keywords: 4. Education